Comparative transcriptome analysis reveals the involvement of an MYB transcriptional activator, SmMYB108, in anther dehiscence in eggplant - Hu, Ruolin; Wang, Jiali; Yang, Huiqing; Wei, Dayong; Tang, Qinglin; Yang, Yang; Tian, Shibing; Wang, Zhimin (Frontiers in Plant Science, 2023)
Male sterility is a highly attractive agronomic trait as it effectively prevents self-fertilization and facilitates the production of high-quality hybrid seeds in plants. Timely release of mature pollen following anther dehiscence is essential for stamen development in flowering plants. Although several theories have been proposed regarding this, the specific mechanism of anther development in eggplant remains elusive. In this study, we selected an R2R3--MYB transcription factor gene, SmMYB108, that encodes a protein localized primarily in the nucleus by comparing the transcriptomics of different floral bud developmental stages of the eggplant fertile line, F142. Quantitative reverse transcription-polymerase chain reaction revealed that SmMYB108 was preferentially expressed in flowers and its expression increased significantly on the day of flowering. Overexpression of SmMYB108 in tobacco caused anther dehiscence. In addition, we found that SmMYB108 primarily functions as a transcriptional activator via C-terminal activation (amino acid262-317). Yeast one-hybrid and dual-luciferase reporter assays revealed that genes (SmMYB21, SmARF6 and SmARF8) related to anther development targeted the SmMYB108 promoter. Overall, our results provide insights into the molecular mechanisms involved in the regulation of anther development by SmMYB108.